Polarization and ellipticity of high-order harmonics from aligned molecules generated by linearly polarized intense laser pulses - Le, Anh-Thu; Lucchese, R. R.; Lin, C. D. (My University, 2010)
We present theoretical calculations for polarization and ellipticity of high-order harmonics from aligned N2, CO2, and O2 molecules generated by linearly polarized lasers. Within the rescattering model, the two polarization amplitudes of the harmonics are determined by the photo-recombination amplitudes for photons emitted with polarization parallel or perpendicular to the direction of the same returning electron wave packet. Our results show clear species-dependent polarization states, in excellent agreement with experiments. We further note that the measured polarization ellipse of the harmonic furnishes the needed parameters for a “complete” experiment in molecules.